2022
DOI: 10.1093/ije/dyac074
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the transparency of reporting in two-sample summary data Mendelian randomization studies using the MR-Base platform

Abstract: Background Two-sample Mendelian randomization (2SMR) is an increasingly popular epidemiological method that uses genetic variants as instruments for making causal inferences. Clear reporting of methods employed in such studies is important for evaluating their underlying quality. However, the quality of methodological reporting of 2SMR studies is currently unclear. We aimed to assess the reporting quality of studies that used MR-Base, one of the most popular platforms for implementing 2SMR an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…2) That there is no sample overlap. The effect of the second assumption is to make weak instrument bias deflationary (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…2) That there is no sample overlap. The effect of the second assumption is to make weak instrument bias deflationary (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…For readers less familiar with the MR literature, it is worth noting that the intercept-free weighted regression is equivalent to an inverse variance weighted meta-analysis of the IV Wald ratios for each SNP. In addition, (1) and (2) only used the first 50 simulated SNPs (i.e. those which associated with the exposure), while (3) used all 100 simulated SNPs (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most popular resources for conducting MR analyses is the UK Biobank (UKB) (2). The UKB is a large (approximately half a million participants) population cohort study of Britons.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 116 articles included in the study, 65% (75) completely reported the genetic variants and weights used to construct the IV, while 9% (10) partially reported this and 27% (31) did not. 40% (46) reported that variants were identified in a different sample as that used in the analysis, or externally weighted, 10% (12) reported only that variants were identified in the same sample and unweighted or identified and weighted in a larger sample which includes the sample used in the MR analysis, 7% (8) reported that variants were identified and weighted from the same sample used in the MR analysis and 43% (50) did not report enough detail to assess this. Whether the variants used had been independently replicated had lower reporting quality across articles; 9% (10) of articles reported that variants were independently replicated, while 8% (9) reported they were partially replicated (eg, replicated in a partially overlapping sample), 13% (15) used unreplicated variants and 71% (82) did not report this.…”
Section: Reporting IV Informationmentioning
confidence: 99%